(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
People are getting more aware about the potential capabilities of a visually impaired person. Thus, with the growing awareness of the abilities of the visually impaired population, few business houses are coming forward in including a visually impaired person in their workforce. Advanced Computer Training Course(ACTC) conducted by TCS, as a part of their CSR program, to empower the visually impaired population is one of its kind initiative. Through this paper the researcher aims to analyse the efficiency of CSR programme in empowering the visually impaired population, by conducting survey on 60 trainees from Mumbai centre. The findings states that there has been a significant improvement on the employment front after the training program. It is noteworthy that as much as 60% of the trainees were unemployed prior to the training, against a mere 33.3% unemployment post the training.